Discussing Sexuality With Women Considering Risk-Reducing Salpingo-oophorectomy: An International Survey of Current Practice in Gynecologic Oncology. Issue 7 (1st September 2016) - Tucker, Paige E.; Bulsara, Max K.; Salfinger, Stuart G.; Tan, Jason Jit-Sun; Green, Helena; Cohen, Paul A.
Abstract : Objective: To determine how frequently gynecologic oncologists discuss sexuality with women considering risk-reducing salpingo-oophorectomy. Secondary objectives were to assess the availability of resources, and the barriers to discussing sexuality. Methods: Members of the Australian Society of Gynaecologic Oncologists, International Gynecologic Cancer Society, and Society of Gynecologic Oncology were invited to complete an online survey. Questions addressed frequency of, and barriers to, discussing sexuality, and availability of resources related to sexual issues. Results: Three hundred eighty-eight physicians in 43 countries responded from 4, 006 email invitations (9.7%). Ninety-one percent reported discussing sexuality preoperatively, and 61% discuss it with every patient. Factors associated with higher rates of discussion were female sex ( P = 0.020), higher level of training ( P = 0.003), time in practice ( P = 0.003), and consulting more risk-reducing salpingo-oophorectomy patients per month ( P = 0.006). Commonly discussed issues were vasomotor menopausal symptoms (91%) and vaginal dryness (85%). Eighty-eight percent of respondents believed that sexuality should be discussed preoperatively, and most felt that it is their responsibility (82%). Fear of causing distress was the most common barrier to discussing sexuality (49%). Twenty-four percent felt that they did not have adequate training to discuss sexual function. Conclusions: Although most respondents believed that discussing sexuality should occur preoperatively, only 61% discuss this with every patient. Resources specifically relating to sexuality are limited. The most common barrier to discussing sexuality was fear of causing distress. Nearly one quarter of gynecologic oncologists felt inadequately trained to discuss sexual function.